High Occurrence of Bacterial Competition Among Clinically Documented Opportunistic Pathogens Including Achromobacter xylosoxidans in Cystic Fibrosis - Menetrey, Quentin; Dupont, Chloé; Chiron, Raphaël; Jumas-Bilak, Estelle; Marchandin, Hélène (Frontiers in Microbiology, 2020)
Cystic Fibrosis (CF) airways favor abnormal microbial development. Infections are considered as polymicrobial and competition can be observed between microorganisms. The current literature on bacterial competition in CF mostly consists of studies with limited numbers of strains, mainly focused on the major pathogens Pseudomonas aeruginosa (Pa) and Staphylococcus aureus (Sa) and does not give a comprehensive overview of the overall importance of bacterial interactions or the behavior of less often encountered emerging bacteria such as Achromobacter. In this context, we screened a panel of 39 strains from 6 CF patients, of either clinical or domestic environmental origin, distinguished according to genotype and belonging to 4 opportunistic pathogens, Pa (n=15), Sa (n=3), Stenotrophomonas maltophilia (Sm, n=10) and Achromobacter xylosoxidans (Ax, n=11). We investigated their capacity to compete in terms of growth, motility and pigment production on agar media through 203 crossing experiments. Eleven strains selected via the initial screening results were further studied for competitive growth in liquid medium and biofilm formation. Competition was noted for 33% (67/203) of the pairs of strains with 85 modifications observed between monocultures and co-cultures, impacting growth (23.6%), motility (13.8%) and/or pigment production (6.1%). Under all conditions of the study (clinical, environmental strains; intra-, inter-patients; intra-, inter-species levels), competition was significantly more frequent among pairs of strains with at least one clinical strain. While Pa mainly outcompeted other species, in one patient with chronic colonization by Ax and sporadic colonization by Pa, we showed that some Ax inhibited the growth and pigmentation of Pa whereas biofilm formation was drastically reduced. Enlarging the panel of strains tested in competition assays gave new perspectives on the complex interactions taking place among the CF airway community. Indeed, the frequent occurrence of varied, strain-dependent interactions is revealed here. We report the first results of competition assays for Ax with the ability of certain strains to outcompete Pa. Our results are linked to the patient’s colonization history and question the importance of bacterial competitiveness in the colonization pattern of CF airways.